Plasma particles drifting in the equatorial plane of quantitative magnetospheric model and related magnetospheric phenomena - Ondoh, Tadanori; Aikyo, Kazuhiro (1985)
P(論文) Using the quantitative magnetospheric model derived by MEAD and FAIRFIELD (J. Geophys. Res., 80,523,1975) from satellite observations of the magnetic field, we have computed equatorial profiles of the total geomagnetic field, electric equipotential lines and drift paths of plasma particles with pitch angle of 90° in the magnetosphere under the superquiet (SQ) and superdisturbed (SD) conditions in case of the magnetospheric tilt angle of 0°. The uniform dawn to dusk electric field used is 0.1mV/m for a quiet time and 0.4mV/m for a disturbed time. All particles start from geocentric circles of 17 earth's radii (R_E) in the equatorial plane of the tail region. Electric equipotential lines in the equatorial plane of the Mead-Fairfield (MF) model are concave on the dawn and dusk sides since the geomagnetic field lines of the MF model in the equatorial plane are curved greatly tailwards on the dawn and dusk sides compared with the radial field lines of a dipole model. The Alfven layer or the boundary of the forbidden region for the zero-energy particles computed in the MF magnetospheric model is compared with the average location of the plasmapause in the equatorial plane. The computed drift paths of zero-energy particles for the uniform dawn to dusk electric field of 0.1mV/m show a stagnation region in the late evening sector which agrees well with the plasmapause bulge observed by ground whistlers. The trapped particle region for zero-energy particles and energetic electrons in the late-evening outer magnetosphere seems to be produced by the particle drift motion in the late-evening outer magnetosphere, where the geomagnetic field lines are greatly curved tailwards under a weak dawn to dusk electric field of 0.1mV/m. The dayside extent of equatorial drift paths for electrons with 0.5keV/nT in the MF-SQ and MF-SD geomagnetic fields for the dawn to dusk electric field of 0.4mV/m corresponds well with the hard electron precipitation region associated with the active mantle aurora. departmental bulletin paper